Serum 25 (OH) D levels and risk of female-specific cancer in premenopausal women: a prospective study - Hu, Yue; Zhu, Chen; Qin, Yingyi; Zhu, Ying; Zhang, Jianzheng; Tong, Qiang; Cai, Shengyun (Frontiers in Nutrition, 2025)
BackgroundSerum 25 (OH) D levels are associated with various diseases, including cancers, but inconsistencies exist for female-specific malignancies. This study is aimed to explore the real relationship between serum 25 (OH) D levels and incidence rates of female specific cancers in premenopausal women by a large-scale prospective cohort study.Study designWe analyzed data from 51,286 UK Biobank participants using Cox regression models to explore associations. Subgroup analyses were based on vitamin D supplementation, alcohol, smoking, BMI, diabetes, sleep, and outdoor exposure. Categorical variables were described by frequencies and compared with chi-squared tests.ResultsDuring a median follow-up of 13.8 years, all cancer incidence was 5.1% (n = 2,614), with ovarian cancer at 0.3% (n = 176), breast cancer at 4.4% (n = 2,232), and uterine body cancer at 0.5% (n = 235). Low serum 25 (OH) D (50 nmol/L) was linked to increased risks of ovarian (HR: 1.457, 95% CI: 1.047–2.027) and uterine body cancer (HR: 1.372, 95% CI: 1.023–1.841). Each 10 nmol/L increase in 25 (OH) D reduced ovarian cancer risk (HR: 0.904, 95% CI: 0.835–0.979). Alcohol use and sleep <6 h were risk factors for ovarian and uterine cancer in those with low 25 (OH) D levels.ConclusionMaintaining adequate serum 25 (OH) D levels is essential for overall health, reducing the risk of ovarian cancer, and potentially lowering susceptibility to uterine corpus cancer.